2013
DOI: 10.2298/bah1304727w
|View full text |Cite
|
Sign up to set email alerts
|

Review of the physiological and pathological welfare indicators applied in turkeys (Meleagris gallopavo)

Abstract: Concern on animal welfare has become an important issue in Europe for a decade now. In commercial poultry husbandry, there are many trials to standardize the production in order to reduce the economic loss caused by poor welfare at marketing age. As it known, factors such as density, group size, space availability, maturation, lighting, feeding, and transportation can have effects on welfare of turkeys. However, to ensure a better quality of live for the birds as well as the industry as good performance, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Monitoring FPD is an accepted tool not only in Germany but all over Europe and the United States [see ( 19 ) for the United Kingdom and the United States, ( 20 , 21 ) for Europe]. Watanabe et al ( 22 ) identified FPD as one of the most relevant animal-based indicators to measure animal welfare so far. This indicator not only provides information on animal health and wellbeing, but is also associated with the husbandry system, with litter quality being the major determinant for this pathology ( 23 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring FPD is an accepted tool not only in Germany but all over Europe and the United States [see ( 19 ) for the United Kingdom and the United States, ( 20 , 21 ) for Europe]. Watanabe et al ( 22 ) identified FPD as one of the most relevant animal-based indicators to measure animal welfare so far. This indicator not only provides information on animal health and wellbeing, but is also associated with the husbandry system, with litter quality being the major determinant for this pathology ( 23 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the evidence that FPD is painful (Martland, 1984;Hocking and Wu, 2013;Sinclair et al, 2015;Weber Wyneken et al, 2015), it is used as an animal welfare indicator in research, on farms, and in slaughterhouses (Watanabe et al, 2013). To illustrate the importance of FPD, United Kingdom supermarkets have identified FPD as a key welfare indicator in turkeys (Clark et al, 2002), and most animal welfare audits in Europe and the United States consider FPD an indicator of impaired welfare (Berg, 2004;Berg and Algers, 2004).…”
Section: Introductionmentioning
confidence: 99%